Principles of mental health care during the COVID-19 pandemic. Issue 1 (2020) - Kuzman, Martina Rojnic; Curkovic, Marko; Wasserman, Danuta
Abstract: We describe the basic principles of mental health care during the COVID-19 pandemic that should be endorsed by the mental health professional associations and incorporated in the health strategies for the management of the COVID-19 pandemic. The main principle is that there should be no substantial differences in the provision of health care for COVID-19 between persons with pre-existing mental health disorders and the ones without previous disorders. Subsequently, the organization of the health care should reflect that as well. These principles should (a) prevent the possible effects of stigmatizing attitudes toward mental health issues, possibly leading to potentially deleterious situations, such as psychiatric patients being treated (even temporarily) separately from other patients, in psychiatric facilities, where the staff is not equipped and trained adequately for the management of COVID-19; (b) highlight the fact that patients with mental health disorders are at greater risk for developing serious complications of COVID-19 infection due to other factors—they often smoke and have comorbidities such as hypertension, diabetes, all associated with higher morbidity and mortality from COVID-19 infection; (c) highlight that measures should be taken to minimize the risk of the spread of infection in psychiatric wards/institutions; (d) provide a general framework for the reorganization of mental health services toward the provision of services for persons in need, including frontline medical workers and patients with COVID-19 without previous mental health problems as well as for persons with pre-existing mental health problems under new circumstances of pandemic.